Criminal Face Sketch Construction and Identification System (International Journal of Scientific Research in Science and Technology, 2025)
In forensic science, traditional hand-drawn facial sketches remain a time-consuming and restrictive method, especially when integrating modern technology for suspect identification. This paper presents an innovative software solution that streamlines the process by enabling users to create composite images of suspects without relying on a forensic artist. Through an intuitive drag-and-drop interface, users can systematically assemble facial features to generate an accurate depiction of the suspect. Once completed, the system swiftly analyzes the composite image against an extensive police database. By harnessing advanced neural network algorithms and robust cloud computing, this approach ensures rapid and highly precise suspect identification.